Firm Size on Profitability: A Comparative Study of Bank of Ceylon and Commercial Bank of Ceylon Ltd in Srilanka - Velnampy, T.; Nimalathasan, B. (My University, 2010)
The banking organizations, today, is moving towards the goal of integrated financial services because of the strong competition and quick changes of technology. In developing countries like Sri Lanka, banking organizations provide fund for other organizational developments. The financial sector in Sri Lanka started as a part of their overall economic plans and growth. Accordingly the banking sector is considered to be an important source of financing for most businesses. This study is initiated to effect of the firm size on profitability of virtually all the branches of Bank of Ceylon (BOC) and Commercial Bank of Ceylon Ltd (CBC) with 10 years accounting period: 1997-2006.Correlation analysis shows that, there is a positive relationship between Firm size and Profitability in Commercial Bank of Ceylon Ltd, but there is no relationship between firm size and profitability in Bank of Ceylon.